Impaired overload-induced muscle growth is associated with diminished translational signalling in aged rat fast-twitch skeletal muscle - Thomson, David M.; Gordon, Scott Edward (East Carolina University, 2006)
Impaired overload-induced protein synthesis and growth in aged fast-twitch skeletal muscle may result from diminished responsiveness of signalling intermediates controlling protein translation. Yet, potential age-related signalling decrements have never been examined in direct parallel with impaired overload-induced muscle growth in any model. To this end, we used Western blotting to examine the contents and phosphorylation states of mammalian target of rapamycin (mTOR) and its downstream translational signalling intermediates, 70 kDa ribosomal protein S6 kinase (S6k), ribosomal protein S6 (rpS6), eukaryotic elongation factor 2 (eEF2), and eukaryotic initiation factor 4E-binding protein 1 (4E-BP1), in conjunction with impaired growth in 1 week overloaded fast-twitch plantaris muscles (via unilateral gastrocnemius ablation) of old (O; 30 months) versus young adult (YA; 8months) male Fischer344 X Brown Norway rats. The significantly (P less than or equal to 0.05) diminished growth (assessed by total muscle protein content) in overloaded O muscles (5.6±1.7 versus 19.3±2.9% in YA) was accompanied by significant impairments in the phosphorylation states of mTOR (Ser2448), S6k (impaired at the mTOR-specific Thr389 residue but not at Thr421/Ser424), rpS6 (Ser235/236) and 4E-BP1 (gel shift), as well as deficits in total eEF2 accretion. Moreover, in overloaded muscles across both age groups, phospho-S6k at Thr389 (but not at Thr421/Ser424), 4E-BP1 phosphorylation status, and total eEF2 accretion were all positively correlated with percentage muscle hypertrophy, and negatively correlated with the phosphorylation (Thr172) of 5 -AMP-activated protein kinase (AMPK; which inhibits translational signalling and protein synthesis in young muscle at rest). As previously published by ourselves, AMPK was hyperphosphorylated in O versus YA muscles used in the current investigation. The present results provide solid evidence that impaired overload-induced growth in aged fast-twitch muscle may partly result from multiple-level decrements in signalling pathway(s) controlling protein translation, and also provide an initial indication that AMPK hyperactivation with age may potentially lie upstream of these decrements. Originally published Journal of Physiology, Vol. 574, Pt. 1, July 2006
Keywords: Overload induced growth; Skeletal muscle; Protein translation